The accurate use of Chinese : practical sentence structures and word usage for English speakers - Teng, Wen-Hua, 1956- (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"The Accurate Use of Chinese is a unique learning resource for learners of Chinese who are English speakers. The primary goal is two-fold: to help these learners leverage their existent knowledge in English and navigate the Chinese system with fewer obstacles; and also to help them prevent errors of which the underlying cause may be English. This is done through comparisons of selected grammar topics, language rules and word usages between the two languages. Grammar topics in English serve as the comparison points from which learners can gain a deeper understanding of the comparable, but differing structures in Chinese. The book's comparative approach is unique and innovative, designed to build a more nuanced and instinctive approach to grammar. A valuable resource for beginners to advanced learners and instructors of Chinese, the book contextualizes grammar structures and provides in-depth information not covered in Chinese language textbooks"--
How to use because in Chinese -- Complex sentences -- Contrasts and Contradictions -- Infinitive (to verb) and "adjective noun" as adjectives -- Information sequence -- The representations of it in Chinese -- Linking verbs and their Chinese counterparts -- Omission and replacement of nouns or pronouns -- The Chinese representations of English past tense and present perfect tense -- English and Chinese prepositional phrases: word orders and grammatical features -- Comparing the use of basic punctuation in English and Chinese -- Conditional sentences, the Subjunctive mood and using if -- Almost -- Already -- First -- Happy -- Live -- Must -- Once -- Only -- Or -- Since -- Some -- Then.
Includes index.
Keywords: Chinese language -- Textbooks for foreign speakers -- English; Chinese language -- Grammar; Mandarin dialects -- Grammar; FOREIGN LANGUAGE STUDY / General; FOREIGN LANGUAGE STUDY / Chinese; LANGUAGE ARTS & DISCIPLINES / Grammar